Cyber Attacks Targeting Android Cellphones - Varol, Nurhayat; Aydogan, Ahmet Furkan; Varol, Asaf (Ieee, 2017)
Mobile attack approaches can be categorized as Application Based Attacks and Frequency Based Attacks. Application based attacks are reviewed extensively in the literature. However, frequency based attacks to mobile phones are not experimented in detail. In this work, we have experimentally succeeded to attack an Android smartphone using a simple software based radio circuit. We have developed a software Primary Mobile Hack Builder to control Android operated cellphone as a distance. The SMS information and pictures in the cellphone can be obtained using this device. On the other hand, after launching a software into targeting cellphone, the camera of the cellphone can be controlled for taking pictures and downloading them into our computers. It was also possible to eavesdropping the conversation.
5th International Symposium on Digital Forensic and Security (ISDFS) -- APR 26-28, 2017 -- Tirgu Mures, ROMANIA
Keywords: Primary Mobile Hack Builder; Application Based Mobile Attackers; Frequency Based Mobile Attackers